Comparing a series of 8-quinolinolato complexes of aluminium, titanium and zinc as initiators for the ring-opening polymerization of rac-lactide1. Issue 27 (21st July 2015) - Bakewell, Clare; Fateh-Iravani, Giovanna; Beh, Daniel W.; Myers, Dominic; Tabthong, Sittichoke; Hormnirun, Pimpa; White, Andrew J. P.; Long, Nicholas; Williams, Charlotte K.
<x xml:space="preserve">Abstract</x> The preparation, characterization and properties of a series of 8-hydroxy quinolinolate complexes of Ti(iv), Al(iii) and Zn(ii) are presented. The complexes are active initiators for rac-lactide polymerizations: their performances are compared.